Ten‐year trends in cardiac implantable electronic devices in New Zealand: a national data linkage study (ANZACS‐QI 51). Issue 4 (13th April 2022) - Foo, Fang Shawn; Stiles, Martin K.; Lee, Mildred; Looi, Khang‐Li; Clare, Geoffrey C.; Webber, Matthew; Boddington, Dean; Jackson, Rod; Poppe, Katrina K.; Kerr, Andrew J.
Abstract: Background: Implant rates for cardiac implantable electronic devices (CIED), including permanent pacemakers (PPM) and implantable cardioverter defibrillators (ICD), have increased globally in recent decades. Aims: This is the first national study providing a contemporary analysis of national CIED implant trends by sex‐specific age groups over an extended period. Methods: Patient characteristics and device type were identified for 10 years (2009–2018) using procedure coding in the National Minimum Datasets, which collects all New Zealand (NZ) public hospital admissions. CIED implant rates represent implants/million population. Results: New PPM implant rates increased by 4.6%/year ( P < 0.001), increasing in all age groups except patients <40 years. Males received 60.1% of new PPM implants, with higher implant rates across all age groups compared with females. The annual increase in age‐standardised implant rates was similar for males and females (3.4% vs 3.0%; P = 0.4). By 2018 the overall PPM implant rate was 538/million. New ICD implant rates increased by 4.2%/year ( P < 0.001), increasing in all age groups except patients <40 and ≥ 80 years. Males received 78.1% of new ICD implants, with higher implant rates across all age groups compared to females. The annual increase in age‐standardised implant rates was higher in males compared with females (3.5% vs 0.7%; P < 0.001). By 2018 the overall ICD implant rate was 144/million. Conclusion: CIED implant rates have increased steadily in NZ over the past decade but remain low compared with international benchmarks. Males had substantially higher CIED implant rates compared with females, with a growing gender disparity in ICD implant rates.